Intertidal pool fish Girella laevifrons (Kyphosidae) shown strong physiological homeostasis but shy personality: The cost of living in hypercapnic habitats. Issue 1 (15th May 2017) - Benítez, S.; Duarte, C.; Opitz, T.; Lagos, N.A.; Pulgar, J.M.; Vargas, C.A.; Lardies, M.A.
Abstract: Tide pools habitats are naturally exposed to a high degree of environmental variability. The consequences of living in these extreme habitats are not well established. In particular, little it is known about of the effects of hypercanic seawater (i.e. high p CO2 levels) on marine vertebrates such as intertidal pool fish. The aim of this study was to evaluate the effects of increased p CO2 on the physiology and behavior in juveniles of the intertidal pool fish Girella laevifrons . Two nominal p CO2 concentrations (400 and 1600 μatm) were used. We found that exposure to hypercapnic conditions did not affect oxygen consumption and absorption efficiency. However, the lateralization and boldness behavior was significantly disrupted in high p CO2 conditions. In general, a predator-risk cost of boldness is assumed, thus the increased occurrence of shy personality in juvenile fishes may result in a change in the balance of this biological interaction, with significant ecological consequences. Highlights: Intertidal fish were exposed to hypercapnic conditions (high pCO2 levels). Hypercapnic conditions did not affect fish's oxygen consumption. Hypercapnic conditions did not affect fish's absorption efficiency. Hypercapnic conditions affected fish's lateralization and boldness behavior.